Postbiotics as natural antimicrobials: a novel biocontrol strategy for food safety - Erdinc, Ayse Nur; Cufaoglu, Gizem (Frontiers in Bacteriology, 2026)
Postbiotics are preparations of inanimate microorganisms and/or their components, with or without associated metabolites or cell structures, that confer health benefits to the host. Compared to probiotics, postbiotics offer enhanced safety, stability, and processing benefits for food applications. Their antimicrobial activity is mainly attributed to compounds like bacteriocins, organic acids, enzymes, and peptides, which can inhibit spoilage and pathogenic microorganisms and suppress biofilms. Lactic acid bacteria–derived cell-free supernatants and similar metabolite-rich preparations have been increasingly applied to foods to control foodborne pathogens and spoilage. This review highlights the emerging role of postbiotics as biocontrol agents in food safety, emphasizing their antimicrobial properties, while also outlining their definition, development, legal status, and current evidence on functionality.